THE TRAJECTORY OF POSTREVOLUTIONARY RUSSIAN DIASPORA THOUGHT AND ITS RELATIONSHIP TO RUSSIAN EXCEPTIONALISM (Религиски дијалог и соработка, 2023)
Attention is being paid to the rise of post-Soviet nationalism, particularly giventhe conflict in Ukraine. To this end, the present paper examines Russian thought and itsrelationship to exceptionalism in the context of the post-Revolutionary diaspora. Examiningthe prevailing approach taken to freedom of thought, in light of Nikolai Berdyaev, Fr.Sergius Bulgakov and other thinkers, a trajectory can be identified that departs from theexceptionalist narrative. In the diaspora, this was accented by emergence in the contextof the ecumenical movement and the keenness demonstrated by the emigres, which wasfitting to the East / West interaction of the movement. In an important sense, the notionof Sobornost emerged as a sign of the diaspora’s theological development – in light theevolution of the notion and its ecclesiological aspect, but also in the journal by the samename, which was published under the auspices of the Fellowship of St. Alban and St. Sergius.This altogether demonstrates a trajectory of thought that emerged in the diasporaintelligentsia, which stood in opposition to exceptionalism, messianic or nationalist sentiments,inasmuch as it was a inheritor of pre-Revolutionary Russian thought, is a contrastto the post-Soviet milieu.